Design procedure for dual air handling unit of air-conditioning system - Azizuddin, Abd Aziz; Sumiyoshi, Daisuke; Akashi, Yasunori (EDP Sciences, 2018)
The use of conventional air-conditioning system in tropical climate is ineffective to reduce the humidity. In a typical application, the indoor temperature has to be overcooled to decrease the humidity which has an inherent effect of high energy consumption. The introduction of dual air handling unit (AHU) is the answer to high humidity environment. Each AHU is tasked to control the parameter of temperature and humidity respectively according to the desired value. In this paper, the objective is to design the procedure of sizing the dual AHU so that the control system could run efficiently. Basically, eight (8) steps are necessary to size the dual AHU system and the procedure requires sequential manner. Namely, the design process are indoor design condition, fresh air flow, outdoor design condition, room cooling load, capacity of both AHUs, supply air temperature of second AHU, supply air temperature of first AHU and the enthalpy of both AHUs. The design procedure also requires a psychrometric chart to indicate the air thermal condition throughout the cycle of the air-conditioning system. In conclusion, the proposed design procedure is simple yet effective for the application of dual AHU system to handle the excessive latent heat environment.